AKTIVITAS PENANGKAP RADIKAL BEBAS DARI BATANG PAKIS (Alsophila glauca J. Sm) - Sri Wahdaningsih; Erna Prawita Setyowati; Subagus Wahyuono (Faculty of Pharmacy, Universitas Gadjah Mada, 2011)
Free radical induced oxidative stress that influences the occurrence of various degenerative diseases such as cancer, coronary heart disease and premature aging. In the case that body's antioxidant defense system does not have excessive antioxidants, additional natural antioxidant via food or other nutrients intake is needed. Stems of ferns are known to contain phenolic compounds that are known to have antioxidant activity. A study has been carried out to determine antioxidant potential of stems of ferns of western Borneo origin compared to quercetin as positive control. Initially, material was macerated gradually with wasbenzen followed by methanol. The extract obtained was filtered and evaporated to dryness to give dried wasbenzen extract and methanol extract respectively. Antioxidant properties of extracts were performed by DPPH on TLC. Active (wasbenzen) extract was then partitioned with 80% methanol to give soluble and insoluble fractions. Active (insoluble) fraction was further fractionated by vacuum liquid chromatography using a gradient mobile phase with increasing polarity (wasbezen: chloroform). Fractions obtained were tested antioxidant activity, and isolation was done by preparative TLC. The purity of isolated antioxidant compound was confirmed by TLC, and antioxidant potential was measured spectroscopically with DPPH method. This compound displayed antioxidant activity, but its value was lower than that of quercetin used as a positive control (IC50 178.4 v / s 2.17 microg / mL)